2013
DOI: 10.1177/0307174x1304000804
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nanosized Fillers on the Structure and on the Deformation and Strength Characteristics of Polymer Blends Based on Nitrile Butadiene Rubber and Polyvinyl Chloride

Abstract: The effect of nanosized fillers on the structure and on the deformation and strength characteristics of polymer blends based on nitrile butadiene rubber and polyvinyl chloride was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This, by all appearances, is connected with the fact that coagulation structures of carbon black particles are formed [14], depending on the size of the pores and free volumes. The effective filling of these volumes and pores undoubtedly affects the physical properties of polymer blends modified with small additions [15,16]. With concentrations of 0.1-0.73 wt%, the large pores are filled with the coarse aggregates into which the particles combine up to structure formation.…”
Section: Methodsmentioning
confidence: 99%
“…This, by all appearances, is connected with the fact that coagulation structures of carbon black particles are formed [14], depending on the size of the pores and free volumes. The effective filling of these volumes and pores undoubtedly affects the physical properties of polymer blends modified with small additions [15,16]. With concentrations of 0.1-0.73 wt%, the large pores are filled with the coarse aggregates into which the particles combine up to structure formation.…”
Section: Methodsmentioning
confidence: 99%
“…For a whole number of polymers it has been shown that the introduction of nanoparticles of different chemical structure and shape makes it possible to increase markedly the mechanical characteristics of the composite, its heat resistance, thermal conductivity, etc. [1][2][3][4][5][6][7][8]. However, this question has been studied insufficiently in the case of small additions of nanoparticles [6][7][8].…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8]. However, this question has been studied insufficiently in the case of small additions of nanoparticles [6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation